(untitled) (Revista de Ciências Agroveterinárias, 2007)
intermittent lighting programs for layers rearing in open shelters. It focuses on different lighting programs, the physiological fundaments regarding the lighting stimulation on reproductive behavior and the major research results of this concept. Current scientific information on the issue indicates that intermittent lighting can be used at commercial layers production without reducing their performance. This technique allows reducing hours of artificial lighting in order to stimulate layers reproduction. Therefore, intermittent lighting can decrease egg production cost on tropical countries where open houses are frequently used.